An evaluation of a body image intervention in adolescent girls delivered in single-sex versus co-educational classroom settings. (April 2017) - Dunstan, Candice J.; Paxton, Susan J.; McLean, Siân A.
Abstract: Body dissatisfaction is now recognized as having considerable negative impact on social, psychological, and physical health, particularly in adolescent girls. Consequently, we have developed a six-session co-educational body image intervention (Happy Being Me Co-educational) designed to reduce body dissatisfaction and its risk factors in Grade 7 girls. In addition to evaluating the program's efficacy, we aimed to identify whether girls would benefit equally when it was delivered as a universal intervention to a whole class including both boys and girls (co-educational delivery), or delivered as a selective intervention to girls only (single-sex delivery). Participants were 200 Grade 7 girls from five schools in Melbourne, Australia. Schools were randomly allocated to receive the intervention in single-sex classes ( n = 74), co-educational classes ( n = 73), or participate as a no-intervention control ( n = 53). Girls completed self-report assessments of body dissatisfaction, psychological (internalization of the thin ideal, appearance comparison, and self-esteem) and peer environment (weight-related teasing and appearance conversations) risk factors for body dissatisfaction, and dietary restraint, at baseline, post-intervention, and at 6-month follow-up. Significant improvements in body dissatisfaction and psychological risk factors were observed in the intervention group at post-intervention and these were maintained at follow-up for psychological risk factors. Importantly, no significant differences between universal and selective delivery were observed, suggesting that the intervention is appropriate for dissemination in both modes. Highlights: The efficacy of a 6 session body image intervention was examined in adolescent girls First study to compare co-educational and single-sex classroom delivery Body dissatisfaction and psychological factors were improved after the intervention There were no differences in outcomes between co-educational and single-sex delivery